2018
DOI: 10.1016/j.redox.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide production by lactobacilli promotes epithelial restitution during colitis

Abstract: Inflammatory bowel disease (IBD) is a multifactorial chronic inflammatory disease of the gastrointestinal tract, characterized by cycles of acute flares, recovery and remission phases. Treatments for accelerating tissue restitution and prolonging remission are scarce, but altering the microbiota composition to promote intestinal homeostasis is considered a safe, economic and promising approach. Although probiotic bacteria have not yet fulfilled fully their promise in clinical trials, understanding the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 99 publications
1
42
0
Order By: Relevance
“…Similar Nox-1 mediated results were observed for Lactobacillus plantarum in drosophila [18] , suggesting that these increases in ROS leads to oxidation of key cysteine residues that modify protein confirmation and cellular function as depicted in Fig. 1 A. Additionally, a recent report has shown that certain strains of lactobacilli generate hydrogen peroxide [37] , indicating that some cellular protein oxidation is caused by ROS produced by the luminal bacteria themselves. We tested the supernatants from overnight cultures of several strains of lactobacilli, including two of our separate lab stocks of LGG (ATCC 53103), and found that while strains of Lactobacillus acidophilus or Lactobacillus gasseri produced high levels of hydrogen peroxide, in comparison LGG by itself did not produce high levels of hydrogen peroxide relative to the untreated control ( Fig.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Similar Nox-1 mediated results were observed for Lactobacillus plantarum in drosophila [18] , suggesting that these increases in ROS leads to oxidation of key cysteine residues that modify protein confirmation and cellular function as depicted in Fig. 1 A. Additionally, a recent report has shown that certain strains of lactobacilli generate hydrogen peroxide [37] , indicating that some cellular protein oxidation is caused by ROS produced by the luminal bacteria themselves. We tested the supernatants from overnight cultures of several strains of lactobacilli, including two of our separate lab stocks of LGG (ATCC 53103), and found that while strains of Lactobacillus acidophilus or Lactobacillus gasseri produced high levels of hydrogen peroxide, in comparison LGG by itself did not produce high levels of hydrogen peroxide relative to the untreated control ( Fig.…”
Section: Resultssupporting
confidence: 77%
“…Several lactobacilli strains, which are naturally occurring members of the microbiota and commonly used probiotics, have been shown to generate and/or induce reactive oxygen species (ROS) production [24] , [36] , [37] . We reported that certain strains of lactobacilli, in particular Lactobacillus rhamnosus GG (LGG) can induce rapid, and non-microbicidal generation of ROS within colonic epithelial cells [20] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The H 2 O 2 produced by NPL-99 was not effective against S. aureus , but could be a therapeutic strategy in correcting irritable bowel disease (IBD)-associated dysbiosis by augmenting gut barrier integrity [77]. Moderate barrier strengthening as seen in NPL-99 through TEER measurements [78] supports the notion of a probiotic role for treating leaky gut [79].…”
Section: Discussionmentioning
confidence: 99%
“…as probiotics in the treatment of inflammatory bowel disease (IBD) (Guandalini & Sansotta, 2019). Stimulation of crypt/gland localized NOX1 oxidant generation may be beneficial by sustaining proliferation and restitution (Alam et al, 2014; Coant et al, 2010; Jones et al, 2013; Kato et al, 2016; Singh, Hertzberger, & Knaus, 2018). Intestinal DUOX2 activation is downstream of NOD2 detection of cytosolic muramyl dipeptide, a component of bacteria cell walls (Lipinski et al, 2009).…”
Section: Introductionmentioning
confidence: 99%